Analysis of Marketing Mix Strategy in Increasing Sales Volume at De Vijas Cafe in Tempel Village, Krian District, Sidoarjo Regency (Study at De Vijas Cafe, Tempel Village, Krian District, Sidoarjo Regency) - Nisrina Zein; Sumainah Fauziah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze the marketing mix strategy (7P) implemented by Kafe De Vijas in an effort to increase sales volume using the SWOT analysis approach. The method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The results of the study indicate that Kafe De Vijas has a main strength in the use of the vintage concept which makes it different from other cafes. The main weakness is the location of the cafe which is not strategic and less than optimal promotion. On the opportunity side, the increasing trend of coffee consumption among Generation Z is a great potential for cafe growth. While the biggest threat comes from the many competitors around the operational area. Based on the results of the IFAS and EFAS calculations, Kafe De Vijas is in quadrant I of the SWOT matrix, which shows that the company's position is in a condition that supports an aggressive strategy, namely maximizing strength to seize opportunities. This study concludes that an effective marketing strategy by highlighting the uniqueness of products and services, accompanied by optimization of digital marketing and improvement of infrastructure, is the key to increasing sales volume.